Perancangan Proyek Sistem Informasi Penjualan Printer dan Sparepart berbasis Web Menggunakan Work Breakdown Structure - Fatmawati Fatmawati; Firmansyah Firmansyah; Timotius Liu Sianturi (Sekawan Institut, 2025)
In the era of rapidly developing information technology, CV. Shaqi Multi Solusi as a business entity engaged in the sale of printers and spare parts, the problems currently faced are difficulties in monitoring, managing stock of goods, inefficiency of the information system used in the sales process and currently the business process is still running manually, where customers must come directly to the store or make an appointment with the store owner to make a sales transaction. From these problems, a web-based sales information system was created which was developed with the PHP programming language and for the design of system development using the Software Development Life Cycle (SDLC) model to facilitate the planning and creation of the system. This study produces a web-based printer and spare part sales information system application that can facilitate the process of managing customer data, managing stock data and sales so that it is more effective and efficient in the sales process and based on the results of system testing, the system can run well according to expectations (valid).